The Influence of Environmental Factors on the Human Body and its Prevention (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The study of environmental factors on the human body is extremely relevant, since in recent years, with the development of technological processes, more and more people are suffering from diseases with blurred, vaguely defined clinical conditions of the human body, the formation of which largely depends on various environmental factors. The quality of atmospheric air largely determines the health status of the population and is an active etiological factor in the development of diseases, primarily in children, the elderly, as well as people suffering from chronic diseases of the respiratory system and cardiovascular system. The article provides some recommendations for reducing the harm caused by environmental factors on human health.